Indikasi Persalinan Seksio Sesarea - Sholikhah Wahyu Subekti (Universitas Airlangga, 2018)
According to Health Ministry (2010), 25%-50% of Fertile Women’s death is related to the problems of pregnancy, labor, and childbirth. The government sets up the program Making Pregnancy Safer (MPS), one of which is by caesarean section delivery to reduce the Number of Maternal Mortality. According to Health Ministry at Nofitasari (2011), one of the indicators of quality care in obstetric and gynecology is by Caesarean Section Rate (CSR). For educational hospital or referral hospital the CSR is ≤ 20%, while for non-educational or non-referral hospital is ≤ 15% of total deliveries per year. At Panembahan Senopati Bantul Hospital, there are 3.365 birth cases in 2013 24.63% of them ends with caesarean section delivery. These cases are higher than the standard rate of caesarean section set by Health Ministry for educational or referral hospitals i.e. ≤ 20% of total deliveries per year. The purpose of this study to find out the indications of caesarean section deliveries at Panembahan Senopati Bantul Hospital in 2013. This is a descriptive research with cross sectional design. The location of study is Panembahan Senopati Bantul Hospital. The study is conducted on 2014. The data are taken from the register book of baby births between January 1-December 31 2013. The result shows that the cases of caesarean section at Panembahan Senopati Bantul Hospital was performed on medical indications 97.5%, non-medical indications 2.5%, medical-single indications 90.1%, elective-single 67.2%, and possibility-single 67.1%. Most medical indications were previous caesarean section (22.4%).